(untitled) (Andamios, Revista de Investigación Social, 2012)
During the last decade, indigenous studies show changes in Mexican cities on ways to construct and present ethnographic data, the product of qualitative approaches are no longer restricted to disciplines like anthropology and sociology, but appear as other disciplinary fields pedagogy, linguistics, graphic design and social work. This article presents a review of a selection of work which sets out new topics on the study of indigenous groups in the metropolis and medium-sized cities, highlighting various forms of ethnographic writing.